MATH
posted by Mathew .
Solve by using elimination:
7x  2y =3
2x +y = 4
?????????????????

(1) 7x  2y =3
(2) 2x + y = 4
look to see which variable is easier to get rid of. since the first equation has 2y, multiple the 2nd equation by 2, so that you get 2y. 2y + 2y = 0, so you will have eliminated the y variable
Multiple (2) by 2
2 (2x + y = 4) = 4x + 2y = 8
Add the two equations together
7x  2y = 3
4x + 2y = 8
11x + 0 = 11
11x = 11
x = 1
Substitute x = 1 in either equation (1) or (2) to find y.
7x  2y = 3
7(1)  2y = 3
7  2y = 3
2y = 4
y = 2
To check
substitute x = 1, y = 2
in the other equation (1)
2x + y = 4
2(1) + 2 = 4
2 + 2 = 4
4 = 4
so it's correct 
Thanks a lot:D

you're welcome